Aplikasi Multiplatform Berbasis Budaya Indonesia (BUDI) untuk Siswa Sekolah Dasar - Dessy Setyowati; Adha Maulana (Universitas Negeri Makassar, 2021)
This study aims to produce a multiplatform application based on Budaya Indonesia (BUDI) which is suitable for use in learning in elementary schools. This research is a development research with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The use of a multiplatform application based on Budaya Indonesia (BUDI) as a medium for learning Indonesian culture is expected to introduce Indonesian culture and make students closer to Indonesian culture. The validation results related to media, materials, and education practitioners were 90%, 79.54%, and 92.5% respectively. The results of this multiplatform application trial for individuals and small groups were 91.6% and 97.8%, respectively. The overall percentage results show the high category, so it is suitable for use in learning in elementary schools. The research related to multiplatform applications in learning baesd on Indonesia culture is expected to be used as a reference in the implementation of similar research, especially in efforts to improve learning in elementary school.